Freestyle-Like V-Y Flaps of the Eyebrow: A New Outlook and Indication of an Historical Technique. (21st October 2013) - Leto Barone, Angelo Alberto; Rossi, Matteo; Giunta, Gabriele; Carmisciano, Marco; Di Rosa, Luigi; Toia, Francesca; D'Arpa, Salvatore; Cordova, Adriana
Abstract : The eyebrow region is of utmost importance for facial movement, symmetry, and the overall cosmetic appearance of the face. Trauma or tumor resection often leave scars that may dislocate the eyebrow producing an alteration both in static symmetry of the face and in the dynamic expressivity. The authors present a technique for eyebrow's defects repair using the remaining eyebrow advancement by means of a "freestyle-like" V-Y flap. In the past two years a total of eight consecutive patients underwent excision of skin lesions in the superciliary region and immediate reconstruction with this technique. On histology, six patients were affected from basal cell carcinomas, one from squamous cell carcinoma, and one from congenital intradermal melanocytic nevus. The pedicle of the flap included perforators from the supratrochlear, supraorbital, or superficial temporalis artery. Advancement of the entire aesthetic subunit that includes the eyebrow using a V-Y perforator flap was performed successfully in all cases achieving full, tension-free closure of defects up to 3.0 cm. "Freestyle-like" V-Y flaps should be considered as a first-line choice for partial defects of the eyebrow. The greater mobility compared to random subcutaneous flaps allows to reconstruct large defects providing an excellent cosmetic result.